Knowing you - Peterson, Tracie (Peterson, Tracie. Pictures of the heart, 2023)
"Budding artist May Parker is captivated by the Japanese exhibits at the Alaska-Yukon-Pacific Exposition and longs to know more about her mother's heritage--which her mother refuses to speak of because of the heartache she left behind in Japan. Wanting to experience more of the exhibits, May works as a Camera Girl--but her curiosity leads her into danger when a suit of samurai armor becomes the target of an elusive art forger. After ten years apart, May is reunited with her childhood friend Lee Munro, a police detective assigned to keep a watchful eye on the exposition. Their friendship immediately begins to blossom with hints of something more, but when they become entangled in a dangerous heist involving the samurai armor and their love is threatened, can they overcome the odds against them?" --